Causes of Tunnel Diseases in a Karst Stratum and Remediation Measures: A Case Study - Jiajia, Shen; Hu, Zhang; Li, Wan; Changan, Zhang; Xing, Shao; Zanquan, Lin; Jie, Song (Frontiers in Earth Science, 2022)
Abstract: Highway tunnels operated in karst areas are prone to serious diseases such as water–mud inrush, lining tension and cracks, and road humps. This paper reviews the historical diseases of the tunnel based on the Nanshibi Tunnel project. The cause analysis of the diseases of the Nanshibi tunnel was performed on the basis of a refined geophysical prospecting scheme for the complex karst geological structure environment. A series of comprehensive treatments were conducted to address the tunnel diseases in the karst area. The treatments included surrounding rock grouting, lining replacement, and adding inverted arches. The results show that the refined geophysical prospecting scheme and disease remediation idea for the complex karst geological structure environment proposed herein can realize the full coverage and accurate detection of karst structures, water passage, and tunnel lining diseases. The proposed scheme can effectively solve the technical problems of karst tunnel diseases that occur repeatedly and are difficult to be completely rectified. Finally, specific engineering practice suggestions were proposed for tunnel disease remediation in the karst area.